Effect of sourdough addition and storage time on in vitro starch digestibility and estimated glycemic index of tef bread. (30th October 2018) - Shumoy, Habtu; Van Bockstaele, Filip; Devecioglu, Dilara; Raes, Katleen
Highlights: Sourdough addition has slightly increased estimated glycemic index of fresh breads. Baking caused an increase in RDS but a decrease in SDS and RS contents of tef breads. During storage, the SDS and RS contents of tef bread increased while RDS decreased. Estimated glycemic index of breads decreased as duration of their storage increased. Abstract: The effect of sourdough amount and storage time on starch digestibility and estimated glycemic index (eGI) of tef bread was investigated. The rapidly digestible starch (RDS), slowly digestible starch (SDS) and resistant starch (RS) of 0–30% sourdough fresh tef breads ranged from 49 to 58, 16 to 29 and 20 to 26 g/100 g starch, respectively. Storage of tef breads up to 5 days decreased the RDS by more than 2-fold while SDS and RS increased by 2 and 3 fold, respectively. The eGI for fresh and stored breads ranged from 39 to 89. Addition of sourdough increased the eGI of fresh breads while no uniform pattern was seen in the stored breads. As the storage time increased, all the breads showed a decrease in eGI. In vivo study is necessary to further investigate the effect of sourdough on GI of tef bread.